ANALYSIS OF THE RELEVANCE OF HYMES THEORY TO LANGUAGE LEARNING THROUGH FILM - Nisa, Lia Khairun; Tadjuddin, Shafruddin; Harini Ekowati, Sri (Universitas Muhammadiyah Makassar, 2025)
The background of language research is not only as a communication tool, but also as a reflection of society's culture, values and social norms. So, the presence of language and pragmatics in this research has an important role in revealing more deeply what communication patterns are. This research aims to dig deeply into the analysis of pragmatic studies on aspects of Speaking Dell Hymes. The research method used is descriptive qualitative with data sources Dialogue Script/Miracle in Cell Film Script No. 7 Indonesian version d an viewing the original video of the Film in the Prime Video application, a descriptive analysis research method using data analysis techniques in the Listen Technique, the Note technique, Data collection is collected through Data Transcription: Transcribing recorded data into text form and analyzing it based on the elements of the Speaking model. The analysis results show that this film contains 129 scenes with a duration of 00:00:00 to 02:21:46 (2 hours 21 minutes 46 seconds) with 129 communication segments which show complex and diverse interaction dynamics. There were 108 recorded data settings and scenes, 32 participants, 104 endings or speech objectives, 2 forms of act sequences, 3 key variations (tone and spirit), 2 types of instrumentalities (verbal and nonverbal), 1 interaction norm, and 2 types of delivery genres. The research results show that there are various forms of speech events that reflect the presence of the “speaking” aspect component in Miracle In Cell Film No. 7 Indonesian Version. This analysis makes a theoretical contribution to language learning through pragmatics and sociolinguistics, especially in understanding the social context of language use and increasing communicative competence through authentic media such as films. Thus, the Speaking aspect component can be used to analyze speech events in films that are still relevant using Dell Hymes theory as a knife for analyzing speech events in communication interactions using digital media.